Edukasi Pengenalan Jenis dan Konservasi Echinodermata pada Siswa Sekolah Dasar Kelurahan Molas - L.D. Langoy, Marnix; Veralyn Maabuat, Pience; Rahayu Pujiastuti, Dwi (The Studies of Social Sciences, 2025)
Echinoderms are defined as literally spiny skinned animals. One of the echinoderms that has high economic value and is vulnerable to exploitation is the sea cucumber. Conservation efforts need to be carried out through an educational approach to elementary school students (SD) to foster awareness based on local wisdom, including the conservation of local fauna that has ecological value. Community service activities aim to increase elementary school students’ understanding of echinoderms, and efforts to foster awareness of conservation from an early age through the introduction of echinoderm types, and their role in nature. Community service activities are carried out using a community education approach that aims to increase understanding and awareness. The team applies a problem-solving method consisting of problem identification, solutions, and evaluation. The results of the questionnaire at the beginning (average value of 53%) before being given the material and at the end (average value of 78%) after being given the material show that the level of understanding has increased by 25%. The data indicate that there is a transformation in the understanding and knowledge of elementary school students which is expected to change students’ attitudes and habits towards the environment.